Inducements, contributions, and fulfillment in new employee psychological contracts - Lee, Cynthia; Liu, Jun; Rousseau, Denise M.; Hui, Chun; Chen, Zhen Xiong (Human Resource Management, 2011)
AbstractThis longitudinal study of newly hired Chinese college graduates (N = 143) investigates the effects of contract fulfillment, employee reports of company inducements (organizational support and job rewards), and supervisory reports of individual contributions (job performance and extra‐role citizenship behavior) upon changes in the graduates' psychological contracts. Three survey waves were administered a year apart, starting with the recruits' job offer acceptance. Analyses revealed that employee fulfillment and perceived contributions predicted particular changes in employer psychological contract obligations, whereas employer fulfillment and perceived inducements predicted changes in employee obligations. The effects of inducements on employee obligation changes and contributions on employer obligation changes were mediated by their respective fulfillment measures. Changes in obligations were greater in the first year of employment than in the second. This study yields implications for managing newcomers and researching the initial phase of employment. ©2011 Wiley Periodicals, Inc.